2009
DOI: 10.1161/hypertensionaha.108.125179
|View full text |Cite
|
Sign up to set email alerts
|

Does Wave Reflection Dominate Age-Related Change in Aortic Blood Pressure Across the Human Life Span?

Abstract: Abstract-Aortic systolic and pulse pressure rise with age because of aortic stiffening. Two factors are responsible: a larger incident wave because of increased aortic characteristic impedance and premature return of wave reflection from peripheral sites. This study aimed to determine the relative contribution of each factor before and after age 60 years. Aortic pressure waveforms were generated for 3682 healthy subjects using a generalized transfer function applied to radial pressure waveforms recorded by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 59 publications
10
47
0
4
Order By: Relevance
“…29 The statistically significant interaction terms found in the large model using age as a continuous variable in the interaction terms were comparable to the interaction terms found in the age-and gender-stratified analyses, and supports the results found in these four analyses. However, the choice of a cut point can affect the results as seen with hs-CRP where we found interaction with gender in subjects o60 years but no gender interaction in the large model.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…29 The statistically significant interaction terms found in the large model using age as a continuous variable in the interaction terms were comparable to the interaction terms found in the age-and gender-stratified analyses, and supports the results found in these four analyses. However, the choice of a cut point can affect the results as seen with hs-CRP where we found interaction with gender in subjects o60 years but no gender interaction in the large model.…”
Section: Discussionsupporting
confidence: 78%
“…6,7 This curve shape could indicate a decrease in pulse wave reflection in the elderly. 28 However, Namasivayam and co-workers 29 hypothesised that the attenuation of AIx is due to a larger contribution of the incident pressure wave to the increasing pulse pressure with age and not a decrease in pulse wave reflection. The incident pressure wave increases as the central arteries get stiffer and loose compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the resultant faster PWV causes earlier return of the reflected wave, which augments the aortic pressure in late systole to further increase the maximal systolic pressure and widen the pulse pressure (Namasivayam et al 2009). …”
Section: Difference Between Brachial and Aortic Blood Pressuresmentioning
confidence: 99%
“…It was recently quantified and suggested 10 that the age-related increase of the backward reflected waves, rather than age-induced aortic stiffening per se, is the most important modulator of PP. The Anglo-Cardiff Collaborative study 11 showed that there is an age-dependency regarding the relative contribution of the incident and the reflected wave on central PP. Although backward reflections seem to be important determinants of the age-related PP increase from early on, the contribution of the incident wave is more pronounced after the age of 60 years.…”
Section: Considerations On the Resultsmentioning
confidence: 99%